Digital Financial Transformation on Retail MSME Scalability Through Customer Engagement - Ariefah Sundari; Armanu; Meithiana Indrasari; Sukesi (Indonesian Journal of Business and Entrepreneurship Research, 2026)
This study examines the effects of Digital Financial Inclusion, QRIS Utilization, and Embedded Finance Adoption on Retail MSME Scalability through Customer Engagement. The increasing adoption of digital financial services has created new opportunities for retail micro, small, and medium enterprises (MSMEs) to improve business performance and expand market reach. However, empirical evidence regarding how different dimensions of digital finance contribute to business scalability remains limited, particularly in emerging economies. This study employs a quantitative approach using primary data collected from 250 retail MSME owners who have adopted digital financial services. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that Digital Financial Inclusion, QRIS Utilization, and Embedded Finance Adoption significantly influence Customer Engagement. Digital Financial Inclusion and Embedded Finance Adoption also have significant positive effects on Retail MSME Scalability. Customer Engagement demonstrates the strongest direct effect on scalability. In contrast, QRIS Utilization does not have a significant direct effect on Retail MSME Scalability. These findings suggest that digital payment technology alone is insufficient to drive business growth unless it contributes to stronger customer relationships. The study highlights the strategic role of Customer Engagement in translating digital financial transformation into sustainable business expansion. The results contribute to the growing literature on digital finance and MSME development by providing evidence that customer-centered digital financial strategies are essential for improving scalability in the retail sector.